IMPROVING STUDENTS LISTENING SKILL USING LISTENING PRACTICE: DIRECT LISTENING THINKING ACTIVITY (DLTA) - Eva Cristiani Sinaga; Nihta V. F. Liando; Trully Wungow (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
The purpose of this study is to analyze the effectiveness of using the Direct Listening Thinking Activity (DLTA) learning strategy in improving the listening skills of eighth grade students at SMP Negeri 1 Eris. Direct Listening Thinking Activity (DLTA) is a learning strategy to improve students' understanding of the material being listened to. This study is pre-experimental design used quantitave research in one group pre-test and post-test. The subjects were 22 sttudents of eigth grade. The data were collected by using matchmaking questions wich the sampling students answer the question according to the instruction given by researcher. The result of this study indicates that the mean score of post-test was higer than pre-test. It can proof that the DLTA strategy can improve students listening skill.